A condition called love. 2 - Morino, Megumi (Kodansha, 2023)
Hotaru is a 16-year-old high school first-year who has always been ambivalent about love ... but somehow or another, she's found herself going out with Hananoi-kun, the pretty boy from the class down the hall who, as it turns out, is a little too romantic for his own good. But they're not official yet; they're going out on a trial basis, and once Christmas Day comes, they'll be perfect strangers again. Hotaru was fine with that ... until Hananoi-kun gave her the happiest Christmas Eve of her life. Now, with the deadline just hours away, Hotaru's beginning to have second thoughts ...